The Implementation of Discussion-Comparison with Critical Analysis and Extended Learning Community on Students’ Motivation and Learning Outcomes - Linda Maseta; Mariana Ade Cahaya; Irwandi (Jurnal BIOEDUIN : Program Studi Pendidikan Biologi, 2026)
This study aims to analyze the effect of applying the Discussion-Comparison with Critical Analysis and Learning Community Extended methods on student motivation and cognitive learning outcomes in Biology at SMA Negeri 7 Bengkulu. This study uses a quasi-experimental design with a Nonrandomized Control-Group Pretest-Posttest design. The research sample consisted of two classes, namely the experimental class taught using innovative methods and the control class taught using conventional methods. The research instruments were a validated motivation questionnaire and a multiple-choice cognitive learning outcome test. The data were analyzed using the Mann-Whitney test and N-Gain calculations. The results showed that students in the experimental class had higher learning motivation than those in the control class. In addition, the increase in cognitive learning outcomes in the experimental class was also more significant, with an average N-Gain of 0.7225 (high category), while the control class only reached 0.1020 (low category). These findings prove that integrating critical discussion with practitioner involvement can increase students' motivation, conceptual understanding, and analytical skills. Thus, the use of this method is more effective than conventional learning in improving students' cognitive learning outcomes.